Fish Diversity in a Kumaun Himalayan River, Kosi, at Almora Uttarakhand. India - Selakoti, Babita (International Journal of Scientific Research and Management (IJSRM), 2018)
The present study deals with the ichthyofaunal diversity in the river Kosi at Almora district Uttarakhand. During the whole study period (Jan. 2013 to Dec. 2013) 12 species of fish fauna were observed. All the recorded fish species belonged to the families Cyprinidae and Botinae. Cyprinidae was the dominant family having 9 fish species out of the 12 species. The family Botinae comprised of 3fish species